IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DALAM MENINGKATKAN MUTU PEMBELAJARAN MATA PELAJARAN AQIDAH AKHLAK DI MTs MUHAMMADIYAH - Ahmad Fauziyana; Taqwatul Uliyah; Nur Widiastuti; Ami Latifah (UNISAN JURNAL, 2023)
The implementation of madrasah-based management in improving the learning quality of the Aqidah Akhlak subject at MTs Muhammadiyah is an interesting research topic to discuss. The purpose of this research is to identify the implementation of madrasah-based management that can improve the quality of Aqidah Akhlak learning at MTs Muhammadiyah. This study used a qualitative descriptive method with data collection techniques through interviews and observation. Participants in this study were principals, teachers, and MTs Muhammadiyah students. The results showed that the implementation of madrasah-based management had a positive effect on the quality of Aqidah Akhlak learning at MTs Muhammadiyah. Madrasah-based management helps facilitate a more effective and efficient learning process. This can be seen from the increase in student motivation and their participation in learning, as well as the use of more varied and creative learning methods. Some of the factors that contribute to the successful implementation of madrasah-based management are the commitment of the principal and teachers, student participation in the learning process, and support from students' parents. In conclusion, the implementation of madrasah-based management is an effective way to improve the quality of Aqidah Akhlak learning at MTs Muhammadiyah. This study recommends that MTs Muhammadiyah and other madrasahs consider using madrasah-based management as a strategy to improve the quality of learning.